2022
DOI: 10.5498/wjp.v12.i6.827
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted leptin-fatty acid biosynthesis is an early manifestation of metabolic abnormalities in schizophrenia

Abstract: BACKGROUND Insulin resistance (IR) and impaired energy expenditure (IEE) are irreparable metabolic comorbidities in schizophrenia. Although mechanism(s) underlying IR and IEE remains unclear, leptin and fatty acid signaling, which has profound influence on insulin secretion/sensitivity, glucose metabolism and energy expenditure, could be disrupted. However, no association of plasma leptin with erythrocyte membrane fatty acids, body mass index (BMI), and psychotic symptoms in the same cohort of unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 85 publications
0
0
0
Order By: Relevance
“…Adipocyte-macrophage inflammatory cascade, involving activated monocytes, could be the primary mediator of adipose tissue abnormalities induced by long-term treatment with psychotropic medications in patients with PDs[ 55 , 77 , 84 , 85 ]. In support of this, several studies including our own, have shown that membrane SFAs, fasting glucose, C-reactive protein, and adipokines including adiponectin and resistin are increased but leptin is decreased in patients with recent onset PDs[ 28 , 39 , 57 , 86 - 89 ]. Evidence suggests that while all fatty acids can inhibit adipokine/leptin production, effect of SAFs could be detrimental[ 12 , 57 , 89 , 90 ].…”
Section: Psychotropic Medications Increase Adiposity/obesitysupporting
confidence: 55%
See 4 more Smart Citations
“…Adipocyte-macrophage inflammatory cascade, involving activated monocytes, could be the primary mediator of adipose tissue abnormalities induced by long-term treatment with psychotropic medications in patients with PDs[ 55 , 77 , 84 , 85 ]. In support of this, several studies including our own, have shown that membrane SFAs, fasting glucose, C-reactive protein, and adipokines including adiponectin and resistin are increased but leptin is decreased in patients with recent onset PDs[ 28 , 39 , 57 , 86 - 89 ]. Evidence suggests that while all fatty acids can inhibit adipokine/leptin production, effect of SAFs could be detrimental[ 12 , 57 , 89 , 90 ].…”
Section: Psychotropic Medications Increase Adiposity/obesitysupporting
confidence: 55%
“…In support of this, several studies including our own, have shown that membrane SFAs, fasting glucose, C-reactive protein, and adipokines including adiponectin and resistin are increased but leptin is decreased in patients with recent onset PDs[ 28 , 39 , 57 , 86 - 89 ]. Evidence suggests that while all fatty acids can inhibit adipokine/leptin production, effect of SAFs could be detrimental[ 12 , 57 , 89 , 90 ]. In addition, elevated SAFs in adipocytes and intercalated macrophages can stimulate de novo biosynthesis of ceramides, which can further potentiate inflammatory effect of SFAs in adipose tissue by disrupting adipokine secretion and signaling in patients with PDs[ 21 , 86 , 91 , 92 ].…”
Section: Psychotropic Medications Increase Adiposity/obesitysupporting
confidence: 55%
See 3 more Smart Citations